The Cross-Entropy Method for Policy Search in Decentralized POMDPs - Oliehoek, Frans A.; Kooij, Julian F.P.; Vlassis, Nikos (Informatica)
The Cross-Entropy Method for Policy Search in Decentralized POMDPs